KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, RENTABILITAS, DAN SOLVABILITAS PERBANKAN SYARIAH PADA PT BANK MUAMALAT INDONESIA TBK. PERIODE 2011-2013 - SUCIATI, (Jurnal Akuntansi AKUNESA, 2014)
This research analyzes the performance of Bank Muamalat Indonesia Tbk. The purpose of this research is to know and analyze the financial performance of Bank Muamalat Indonesia Tbk. using liquidity, rentability, and solvency ratio. This research using qualitative method and using data financial report Bank Muamalat Indonesia Tbk. period 2011-2013. The result showed that the Bank Muamalat Indonesia Tbk. have good financial performance, accept ROE, NPM, and DER ratio. That ratio should be increase again and the stockholders will give their financial capital for the bank.Kata Kunci: Kinerja keuangan, Bank Syariah, Likuiditas, Rentabilitas, Solvabilitas